2018
DOI: 10.5935/abc.20180085
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Blood Pressure Variables in Children and Adolescents with Duchenne Muscular Dystrophy

Abstract: BackgroundDuchenne muscular dystrophy is an X-chromosome-linked genetic disorder (locus Xp21). Involvement of the cardiovascular system is characterized by fibrous degeneration/replacement of myocytes with consequent ventricular hypertrophy and arterial hypertension.ObjectiveTo assess, by using 24-hour ambulatory blood pressure monitoring, the behavior of blood pressure variables in children and adolescents with a confirmed diagnosis of Duchenne muscular dystrophy.MethodsProspective observational cohort study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Recent clinical studies have called attention to a critical role for low blood pressure in DMD [47À50]. Specifically, low blood pressure in an ambulatory setting emerged as a distinctive feature of DMD patients [47,49,50]. In a retrospective study of 43 DMD patients [48], Cheeran and coworkers identified low systolic pressure as one of the prognostic factors that predicts a worse outcome and death.…”
Section: Discussionmentioning
confidence: 99%
“…Recent clinical studies have called attention to a critical role for low blood pressure in DMD [47À50]. Specifically, low blood pressure in an ambulatory setting emerged as a distinctive feature of DMD patients [47,49,50]. In a retrospective study of 43 DMD patients [48], Cheeran and coworkers identified low systolic pressure as one of the prognostic factors that predicts a worse outcome and death.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, hemodynamic instability in neuromuscular diseases was observed. BP was lower in patients with Duchenne muscular dystrophy (DMD), a representative neuromuscular disease, than in healthy patients, and this was thought to be due to decreased cardiac function [ 28 , 29 ]. In addition, it is reported that an increase in prothrombin time and depletion of factor VII is more common in NMS than AIS, which can lead to an increase in the bleeding amount [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a patient population of 29 patients they have demonstrated a significant drop in systolic BP, diastolic BP and HR both at rest and on exercise after a period of one month after the surgery. There are also a few older animal and human studies analysing the hemodynamic response of unilateral and bilateral upper thoracic sympathetic denervation [ [32] , [33] , [34] , [35] , [36] , [37] ]. They demonstrated that right and left thoracic sympathetic denervation may produce opposite effects on cardiac arrhythmias in experimental animals and in humans, with left sided sympathectomy producing more drop in BP, shortening of QTc and decrease in HR.…”
Section: Discussionmentioning
confidence: 99%